Exploring Exploring Aceh’s Virtual Destination Image Through Netizen’s Perception on Tiktok : Exploring Aceh’s Virtual Destination Image Through Netizen’s Perception on Tiktok - Mawaddah; Ulfa Erfendy (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2026)
This study examines the virtual destination image of Aceh Province as a halal tourism destination through user interactions on TikTok. Using a qualitative content analysis of 3,960 user comments on the three most highly engaged Aceh tourism videos, the findings reveal that destination image (381 comments) is the dominant theme, indicating that visual appeal natural beauty and aesthetic qualities shapes Aceh's virtual image more strongly than informative narratives. Travel interest emerged as a significant theme (176 comments), demonstrating that visual exposure on TikTok influences visit intention. Netizen sentiment was balanced between positive (92) and negative (86) opinions. Negative comments primarily expressed concerns about Sharia law enforcement for non-local tourists while positive comments emphasized Aceh's cultural uniqueness and religious identity. Islamic and halal values appeared as supporting elements (114 comments) but were secondary to visual representation. Keywords: virtual destination image, halal tourism, Aceh, TikTok, analysis of netizen comments, electronic word of mouth